Tunable Lubricin-mimetics for Boundary Lubrication of Cartilage. (March 2017) - Samaroo, Kirk J.; Tan, Mingchee; Andresen Eguiluz, Roberto C.; Gourdon, Delphine; Putnam, David; Bonassar, Lawrence J.
Abstract: The glycoprotein lubricin is the primary boundary lubricant of articular cartilage. Its boundary lubricating abilities arise from two key structural features: i) a dense mucin-like domain consisting of hydrophilic oligosaccharides and ii) an end terminus that anchors the molecule to articulating surfaces. When bound, lubricin molecules attract and trap water near a surface, reducing friction and facilitating glide. Synthetic analogues were previously created to mimic lubricin using thiol-terminated polyacrylic acid- graft -polyethylene glycol (pAA- g -PEG) brush copolymers. The PEG moiety was designed to mimic the mucin-like domain of lubricin and the thiol-terminus was designed to anchor the molecules to cartilage surfaces, mimicking the binding domain. In this study, these synthetic lubricin-mimetics were bound to gold-coated surfaces to characterize the relationship between the polymers' molecular architecture and their lubricating capacity. A library of nine copolymer brushes was synthesized using different sizes of pAA and PEG. Larger molecular weight polymers created smoother, more densely covered surfaces (p < 0.05). Additionally, the hydrodynamic sizes of the polymers in solution were correlated with their lubricating abilities (p < 0.05). Friction coefficients of cartilage against polymer-treated gold surfaces were lower than cartilage against untreated surfaces (Δμeq = − 0.065 ± 0.050 to − 0.093 ± 0.045, p < 0.05). Highlights: A library of pAA- g -PEG polymers was synthesized to mimic the structure of lubricin. The polymers self-assembled onto gold-coated glass slides. The interaction between the polymers and the gold surfaces were imaged using AFM. Polymers on gold were oscillated against cartilage explants. Larger polymers covered more area and lubricated better.